Program Pemberdayaan Keluarga Dhuafa “Bantuan Modal Usaha Warung Jajan Ibu Enur Warga Kebayoran Lama Selatan” - Irdan Suwardana Yahya; Miftah Anandini; Laila Sabrina; Mulkan Habibi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Poverty in Indonesia is a complex problem involving various economic, social, and political factors. According to data from the Central Statistics Agency (BPS), the percentage of the poor population in Indonesia has decreased, but there are still millions of people living below the poverty line, especially in remote areas with higher poverty rates than urban areas. Empowerment of the dhuafa family is a strategic effort to improve the standard of living and welfare of economically disadvantaged community groups. This empowerment program aims to provide access to resources, education, skills training, and business capital. In a social context, the empowerment of the dhuafa family focuses not only on the economic aspect, but also on increasing the social and psychological capacity of individuals. The method used in the empowerment program is carried out in several stages, namely conducting interviews, observations, and documentation. With the efforts of the dhuafa family empowerment program, it is hoped that Indonesia can reduce poverty and improve the overall welfare of the community.